Nieoczywiste relacje z technologią. Przegląd badań na temat ludzkich postaw wobec robotów - Wasielewska, Aleksandra; Łupkowski, Paweł (Człowiek i Społeczeństwo, 2021)
This paper presents an overview of empirical studies concerning human attitudes towards robots. We start with explaining what attitudes towards robots are. It is followed by the overview of the aforementioned studies which is organized according to the factors related to the attitudes. These are human-related factors (sex, age, education, nationality, culture, belief in human nature uniqueness, religiousness), robot-related ones (external look, its purpose) and factors which arise from the human-robot interaction (earlier experiences with robots, interactions, designing robots).